P019 Are gps treating gonorrhoea appropriately?. (8th June 2017) - Perera, Sean; Gonah, Tamuka; Dean, Gillian
Abstract : Introduction: Gonorrhoea continues to develop progressive antibiotic resistance. It is essential 1 st line therapy is used wherever possible (intramuscular ceftriaxone with azithromycin 1g). GPs make an important contribution to gonorrhoea diagnosis and treatment (~5% of all diagnoses, of which ~40% are treated by GPs, 10% with recommended therapy). Methods: To assess local practice, the department of microbiology provided a database of all the cases of gonorrhoea diagnosed across our city Jan 15–Dec16. We reviewed cases diagnosed in primary care. Results: 1.7% (34/1, 956) of all gonorrhoea cases were diagnosed in primary care. Median age 32 (range 18-66); 18 male, 16 female. 88% (30/34) were registered with sexual health (SH); 19 (56%) had attended for the management of episode in question (two of these had prior treatment with azithromycin 1g, or azithromycin/cefixime). Of the remaining 15 cases: Discussion: Knowledge of correct gonorrhoea management pathways was high. Oral cefixime/azithromycin is no longer recommended 1 st line, however cure can be achieved at an individual level. It is likely some patients without record of attendance visited other services outside our area. The high number of female patients compared with our usual male to female ratio (10:1) raises doubts about false positive results in a low prevalence female population.